2005
DOI: 10.1038/sj.gt.3302462
|View full text |Cite
|
Sign up to set email alerts
|

Variability in infectivity of primary cell cultures of human brain tumors with HSV-1 amplicon vectors

Abstract: We investigated the variability in infectivity of cells in primary brain tumor samples from different patients using an HSV-1 amplicon vector. We studied the infectivity of HSV-1 amplicon vectors in tumor samples derived from neurosurgical resections of 20 patients. Cells were infected with a definite amount of HSV-1 amplicon vector HSV-GFP. Transduction efficiency in primary tumor cell cultures was compared to an established human glioma line. Moreover, duration of transgene expression was monitored in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Theoretical considerations and experimental observations made thus far indicate that mechanisms of tumor resistance to HSV-1 therapy include ECM-mediated impairment of intratumoral virus spread, impaired viral entry into tumor cells because of decreased expression of HSV-1 entry receptors, inhibition of viral replication after viral entry into tumor cells, and virus clearance by the host immune system. [5][6][7][12][13][14][15][17][18] In this study, we found that at least two of these potential mechanisms of virus resistanceimpaired virus spread in the ECM and inhibition of viral replication after viral entry into tumor cells-are also relevant to 3D tumor cell cultures.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Theoretical considerations and experimental observations made thus far indicate that mechanisms of tumor resistance to HSV-1 therapy include ECM-mediated impairment of intratumoral virus spread, impaired viral entry into tumor cells because of decreased expression of HSV-1 entry receptors, inhibition of viral replication after viral entry into tumor cells, and virus clearance by the host immune system. [5][6][7][12][13][14][15][17][18] In this study, we found that at least two of these potential mechanisms of virus resistanceimpaired virus spread in the ECM and inhibition of viral replication after viral entry into tumor cells-are also relevant to 3D tumor cell cultures.…”
Section: Discussionmentioning
confidence: 90%
“…However, observations indicate that potential problems include the impairment of intratumoral virus spread by the extracellular matrix (ECM), decreased expression of viral entry receptors by different tumor cell populations, activation of intracellular tumor defenses to viral infection, and quick virus clearance by the host immune system. 7,[12][13][14][15][16][17][18][19] It is clear that many aspects of the complex virus-host interactions that determine the effectiveness of HSV-1 oncolytic therapy are difficult to impossible to study in traditional 2D tissue culture systems.…”
Section: Introductionmentioning
confidence: 99%
“…February 15, 2007 potential therapeutic efficacy, which nevertheless remains either partial or occurs only in single patients with small tumors. Explanations for the limited therapeutic efficiency include the heterogeneity of target tissue (31), insufficient transduction efficiency (32), and interindividual variability of infectivity by vector particles due to different entry receptor status (8). Ongoing research focuses on the development of safe replication-conditional vectors and genetic approaches to target vascular and growth factor receptors and transforming growth factor-h, as well as to stimulate the immune response.…”
Section: Cancer Researchmentioning
confidence: 99%
“…Localized transduction of brain tumor cells with therapeutic genes may influence their biological properties by rendering them sensitive to prodrugs, altering the expression of cell cycle regulating proteins, inhibiting angiogenesis, stimulating the immune response, or triggering apoptosis. The helper virus-free herpes simplex virus type 1 (HSV-1) amplicon has been shown to be a safe and efficient vector system in culture and in vivo to transduce various central nervous system (CNS)-derived cells including human gliomas (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…82 A recent report described the wide variability of infectivity of primary brain tumor cultures using replication-deficient HSV-1 amplicons, which may explain the different responsiveness of patients to virotherapy. 83 Potential solutions include the use of oncolytic vectors that can propagate throughout the tumor mass.…”
mentioning
confidence: 99%